Normative transformation and the War on Terrorism : the evolution of targeted killing, torture, and private military contracting / Simon Frankel Pratt. - Pratt, Simon Frankel (Cambridge University Press, 2022)
Pratt investigates the potential erosion of prohibiting assassination, torture, and mercenarism during the US's War on Terrorism. In examining the emergence and history of the US's targeted killing programme, detention and interrogation programme, and employment of armed contractors in warzones, he proposes that a 'normative transformation' has occurred, which has changed the meaning and content of these prohibitions, even though they still exist. Drawing on pragmatist philosophy, practice theory, and relational sociology, this book develops a new theory of normativity and institutional change, and offers new data about the decisions and activities of security practitioners. It is both a critical and constructive addition to the current literature on norm change, and addresses enduring debates about the role of culture and ethical judgement in the use of force. It will appeal to students and scholars of foreign and defence policy, international relations theory, international security, social theory, and American politics.